2009
DOI: 10.1038/aja.2009.51
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous p27KIP1 expression induces anti-tumour effects and inhibits the EGFR/PI3K/Akt signalling pathway in PC3 cells

Abstract: Abstractp27 is a cyclin-dependent kinase inhibitor that regulates the progression of cells from G 1 to S phase of the cell cycle. Loss of p27 has been associated with disease progression and with an unfavourable outcome in prostate cancer. In this study, we investigated whether exogenous p27 expression in the human androgen-independent prostate cancer PC3 cell line had any effect on cell growth, and we studied the molecular mechanisms involved. p27 expression was restored in PC3 cells by plasmid delivery. Cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…We also found that the decreased Akt activity corresponds to the enhanced expression of the proapoptotic protein Bad. This is consistent with the results of the studies by Jun et al [ 56 ]. Additionally, studies by Al-Bazz et al found a significant correlation between the expressions of Akt and Bad [ 57 ].…”
Section: Discussionsupporting
confidence: 94%
“…We also found that the decreased Akt activity corresponds to the enhanced expression of the proapoptotic protein Bad. This is consistent with the results of the studies by Jun et al [ 56 ]. Additionally, studies by Al-Bazz et al found a significant correlation between the expressions of Akt and Bad [ 57 ].…”
Section: Discussionsupporting
confidence: 94%
“…Avoiding apoptosis is a hallmark of cancer, and downregulation of p27 is one mechanism by which tumor cells can achieve this goal (48,49,(56)(57)(58). Consistent with this, low levels of p27 are associated with poor prognosis in a number of human cancers, including breast cancer (38,40,48,55).…”
Section: Introductionmentioning
confidence: 59%
“…Specifically, Zhang et al determined the knockdown of linc00152 can inhibit the cell cycle (especially the G1 phase) to delay cell proliferation. This was revealed by the considerable decrease in EGFR, PI3K, and AKT activities and the epithelial intercellular transition via the suppression of fibronectin and vimentin downstream of the EGFR/PI3K/AKT signaling pathway to inhibit cell invasion and migration, in addition to an increase in P21 production to promote apoptosis . This not only clarified the linc00152 mechanism related to the progression of NSCLC but also suggests that linc00152 is a potential therapeutic target.…”
Section: Molecular Functions and Mechanisms Of Linc00152 In Human Tumorsmentioning
confidence: 86%